A challenging case of primary amenorrhoea. (11th July 2018) - Sarathi, Vijaya; Reddy, Ramesh; Atluri, Sridevi; Shivaprasad, Channabasappa
Abstract : The differential diagnosis of a girl presenting with primary amenorrhoea includes numerous conditions. Often, patients of 46XY disorder of sex development (DSD) are reared as girl and present with primary amenorrhoea. Their further evaluation to reach the final diagnosis is often a great challenge. In this article, we report a challenging case of 46XY DSD presented with primary amenorrhoea. Patient had spontaneous breast development which initially confused the diagnosis to complete androgen insensitivity syndrome. However, low testosterone suggested against this possibility and further evaluation revealed hormonal findings consistent with 17α hydroxylase/17, 20 lyase (CYP17A1) deficiency. Patient had 46XY karyotype and in consistence with hormonal findings patient was found to have a likely pathogenic homozygous c.1345C>T (p.Arg449Cys) variation in exon 8 of CYP17A1 .